(untitled) (London, 2007)
This proven and internationally recognized text teaches the methods and ideas of engineering design as a condition of successful product development. It breaks down the design process into phases and then into distinct steps, each with its own working methods. Having established itself, in earlier editions, as a key text, Engineering Design (3rd edition) is enhanced with more input from practising engineers, providing more examples of product development; it also tightens the scientific bases of its design ideas with new solution fields in composite components, building methods, mechatronics and adaptronics and pays attention to the economic aspects of design and development including quality assurance. The third edition also integrates electronic design process technology into its methods.
Keywords: Engineering design,Kỹ thuật thiết kế